2016
DOI: 10.1007/s12471-016-0880-0
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of cardiac pacemakers over a 20-year period: Results from a nationwide pacemaker registry

Abstract: The implantation of cardiac pacemakers has become a well-established therapy for conduction disorders and sinus node dysfunction. In many countries pacemaker registries have been initiated in order to collect information on patient characteristics, trends in numbers and the types of pacemakers used, to identify problematic devices, and for safety monitoring. For this utilisation study the Central Pacemaker Patients Registration (CPPR) from the Netherlands Pacemaker Registry Foundation (CPPR-SPRN) containing da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
1
12
0
6
Order By: Relevance
“…An analysis of Dutch registry data of 96,900 patients undergoing initial pacemaker implantation showed that 32.6% of patients were ≥80 years of age (28). The most common indications for pacemakers were SND (42.3%) and AV block (38.9%).…”
Section: Bradyarrhythmiasmentioning
confidence: 99%
“…An analysis of Dutch registry data of 96,900 patients undergoing initial pacemaker implantation showed that 32.6% of patients were ≥80 years of age (28). The most common indications for pacemakers were SND (42.3%) and AV block (38.9%).…”
Section: Bradyarrhythmiasmentioning
confidence: 99%
“…1 The development of artificial permanent pacemakers (PPMs) for electrical control of cardiac rhythm has greatly enhanced a physician's ability to treat cardiac dysrhythmias including sick sinus syndrome (SSS) and complete atrioventricular block (CAVB) and reduced cardiac morbidity and mortality related to symptomatic bradycardia. 1 The development of artificial permanent pacemakers (PPMs) for electrical control of cardiac rhythm has greatly enhanced a physician's ability to treat cardiac dysrhythmias including sick sinus syndrome (SSS) and complete atrioventricular block (CAVB) and reduced cardiac morbidity and mortality related to symptomatic bradycardia.…”
Section: Introductionmentioning
confidence: 99%
“…An ageing population with increasing prevalence of symptomatic bradycardia will result in an increase in the number of cardiac device implantations worldwide. 1 The development of artificial permanent pacemakers (PPMs) for electrical control of cardiac rhythm has greatly enhanced a physician's ability to treat cardiac dysrhythmias including sick sinus syndrome (SSS) and complete atrioventricular block (CAVB) and reduced cardiac morbidity and mortality related to symptomatic bradycardia. 2 However, chronic right ventricular (RV) pacing-related pacing-induced cardiomyopathy (PICM) has a potentially deleterious effect on left ventricular (LV) performance.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiologists and allied professionals were invited to voluntarily register data of each patient, pacemaker generator, and leads on the former European pacemaker card. Data on symptoms, indication and diagnosis, brand of pacemaker and leads, type, follow‐up visits, explantation, hospital transfer, and death were registered according to the European Registry Guidelines established from 1982 onward …”
Section: Methodsmentioning
confidence: 99%
“…To identify CIED failures, a registry was set up in the Netherlands in the early 1980s: the Central Pacemaker Patients Registration (CPPR) from the Netherlands Pacemaker Registry Foundation (CPPR‐SPRN) . This registry collected data over 25 years and allows for analysis of trends over time regarding the duration of service time or longevity of leads after first implantation . For this paper, the reasons for replacement or extraction of leads were studied.…”
Section: Introductionmentioning
confidence: 99%